INTRASEMIOTIC AND INTRALINGUAL TRANSLATION TECHNOLOGIES: FROM NOVEL TO FILM TEXT - Aleksandr S. Besedin (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2017)
The author studies the problem of transforming the text of a work of fiction during its film adaptation. A fantasy book series by George R.R. Martin, A Song of Ice And Fire, and its HBO adaptation, Game of Thrones series, were chosen as the object of the research. The article provides a comparative analysis of the prologue of the first novel, Game of Thrones, and the opening of the first episode of the series, Winter Is Coming. Using the notions of intralingual translation and intersemiotic translation the means of adapting a fiction text to a film text have been determined, taking into account audiovisual opportunities for representing informational and emotional aspects of the novel. It has been found that the following means are used for adapting the prologue: alternate naming of characters, transposition of events, compression and omission of characters' background, dialogues and the final battle, addition of actions and lines allowing to explain further events. It has been demonstrated that audiovisual sequence compensates the reduction of information verbally represented in the novel text and shapes the intersemiotic space of the film text.